2017
DOI: 10.1093/abbs/gmx026
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent down-regulation of hyperpolarization-activated cyclic nucleotide-gated channel 4 causes deterioration of canine sinoatrial node function

Abstract: The activity of pacemaker cells in the sinoatrial node (SAN) is an indicator of normal sinus rhythm. Clinical studies have revealed that the dysfunction of the SAN progressively increases with aging. In this study, we determined the changes in hyperpolarization-activated cyclic nucleotide-gated channel 4 (HCN4) expression and the relationship between aging and canine SAN dysfunction. The results of cardiac electrophysiological determination revealed that the intrinsic heart rate decreased from 168 ± 11 beats m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Exit block through the SACP can develop in the dog with high levels of acetylcholine corresponding to high vagal tone potentially obtained during sleep (Glukhov et al, 2013;Kalyanasundaram et al, 2019). Although the intrinsic sinus rate of the dog (Evans et al, 1990;Du et al, 2017) and human (Opthof, 2000;Li et al, 2017) are similar, the higher parasympathetic tone in the dog is associated with a more pronounced sinus arrhythmia that we hypothesize based on the identified patterning of intervals in this study is, in part, the consequence of a more profound effect on the SACP resulting in exit block. Moreover, although variations in the non-linear patterns of sinus rhythm were seen in the dog, those with greater clustering of beats with 'shorter' short-long intervals had less variability than those with greater branching suggesting a possible difference in the balance between the rhythmicity of the parasympathetic and sympathetic tone.…”
Section: Different Ways To Speed and Slowmentioning
confidence: 59%
See 1 more Smart Citation
“…Exit block through the SACP can develop in the dog with high levels of acetylcholine corresponding to high vagal tone potentially obtained during sleep (Glukhov et al, 2013;Kalyanasundaram et al, 2019). Although the intrinsic sinus rate of the dog (Evans et al, 1990;Du et al, 2017) and human (Opthof, 2000;Li et al, 2017) are similar, the higher parasympathetic tone in the dog is associated with a more pronounced sinus arrhythmia that we hypothesize based on the identified patterning of intervals in this study is, in part, the consequence of a more profound effect on the SACP resulting in exit block. Moreover, although variations in the non-linear patterns of sinus rhythm were seen in the dog, those with greater clustering of beats with 'shorter' short-long intervals had less variability than those with greater branching suggesting a possible difference in the balance between the rhythmicity of the parasympathetic and sympathetic tone.…”
Section: Different Ways To Speed and Slowmentioning
confidence: 59%
“…How autonomic input is subtracted (e.g., pharmacological blockade, surgical denervation, explanted heart) influences this value (Evans et al, 1990). Also, age is an important determinant of the intrinsic rate with young dogs (168 ± 11 bpm) having faster rates compared to adults (120 ± 9 beats per minute) and elderly (88 ± 9 bpm) dogs (Du et al, 2017).…”
Section: Sacp and Bifurcation Intervalmentioning
confidence: 99%
“…Genes underlying familial and acquired sick sinus syndrome. Familial sick sinus syndrome has been linked to mutations in Hcn4 91 , and acquired sick sinus syndrome in ageing 92 , heart failure 93 , atrial fibrillation 94 , diabetes 95 , pulmonary hypertension 96 and even athletes 11 has been linked to a downregulation of Hcn4. If there is a day-night rhythm in Hcn4 (P = 0.072), this may impact sick sinus syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data from animal models (Alings and Bouman, 1993;Satoh et al, 2005;Jones et al, 2007;Moghtadaei et al, 2016;Du et al, 2017) and human studies (Opthof, 1994;Dobrev, 2009) have demonstrated an association between SND and aging. It has been shown that during the aging process, changes occur to SAN function, manifested by increased pacemaking cycle length (CL) (i.e., slower heart rate) and reduced conduction of action potentials [i.e., an increased sinoatrial node-atrium conduction time (SACT)].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these contribute to the reduced aerobic capacity of older adults, leading to an increased incidence of abnormal pacemaking and atrial arrhythmia (Sharpe et al, 2017). Further investigations have also revealed that such agingassociated SND is related to changes in the cellular electrical properties of the SAN (see Supplementary Table 1 in the Appendix) (Congxin Huang et al, 2006;Zhang et al, 2007;Hao et al, 2011;Larson et al, 2013;Tohno et al, 2014;Huang et al, 2015;Moghtadaei et al, 2016;Du et al, 2017) in a similar way to aging-induced cellular changes in atrial and ventricular cells (Congxin Huang et al, 2006) and intercellular electrical coupling (Jones et al, 2004). A list of aging-related changes in mRNA/proteins of ion channels, Ca 2+ handling, intercellular coupling and tissue fibrosis population of the SAN for different species is given in Supplementary Table 1 in the Appendix.…”
Section: Introductionmentioning
confidence: 99%